If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (47x + 24y) + (35x + 39y) = 0 Remove parenthesis around (47x + 24y) 47x + 24y + (35x + 39y) = 0 Remove parenthesis around (35x + 39y) 47x + 24y + 35x + 39y = 0 Reorder the terms: 47x + 35x + 24y + 39y = 0 Combine like terms: 47x + 35x = 82x 82x + 24y + 39y = 0 Combine like terms: 24y + 39y = 63y 82x + 63y = 0 Solving 82x + 63y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-63y' to each side of the equation. 82x + 63y + -63y = 0 + -63y Combine like terms: 63y + -63y = 0 82x + 0 = 0 + -63y 82x = 0 + -63y Remove the zero: 82x = -63y Divide each side by '82'. x = -0.7682926829y Simplifying x = -0.7682926829y
| 13-10x=121-31x | | x*5=-8 | | 2s+3s-7m+2=17m | | m-7=-13+m | | 9x=8x-31 | | 42j+18-19=-28 | | 5y+8=2y+2 | | 5x=-2 | | 4(x+2)=4x-10 | | 3p-1=3x-9 | | 3x^2+12x= | | -4(1+5X)-7(-5+8X)=31 | | 3(x-5)-14=2(x-7)+2 | | 2(s-3)=15 | | x-3+2=0 | | -5(m+10)=100 | | 4(x+7)=36 | | 30=-2(1+2N)+8(N+8) | | -2x-1=7+2x | | 4(3x+15)=0 | | -3s+(-4)=25 | | -7(-5V+1)+5(8+7V)=33 | | 3s+4=25 | | 2(3x-7)=3x-5 | | X+(-4)=8 | | 2x*x^2-16*4x+3=0 | | 5(6+8B)+8(B-5)=-10 | | m-4m+12=3 | | 5x+10=9x+15 | | [(x-2)-5][(x-2)+3]=0 | | 18+2x=-54 | | 17x+64=13 |